PREGNANCY DIAGNOSIS AS A CONDITION FOR ISLAMIC MARRIAGE APPLICATION IN INDONESIA: MASLAHAH MURSALAH PERSPECTIVE - Mariah Algiftiah (LPPM UNHASY, 2021)
One of the purposes of marriage is to continue the offspring. The premarital pregnancy detection test practiced by KUA is a new breakthrough which is motivated by community concerns because of the increasing prevalence of promiscuity that affects pregnancy outside marriage. Therefore, the author focuses on 3 aspects of the problem in this thesis, namely: (1) How is the implementation of marriage in KUA, Jombang ?, (2) What is the urgency of the prenuptial pregnancy detection test in KUA, Jombang? practice of detecting premarital pregnancy? The type of research in this thesis is field research. The data sources in this study were obtained directly from the field with a qualitative approach in which data was collected and then processed with a descriptive analytical approach. If this policy is linked and analyzed using the theory of maslahah mursalah, the obligation to test prenuptial pregnancy detection is to provide benefits to many parties, namely all parties will be able to know in detail the results of the examination. In addition to providing benefits, this policy can also reject adversity that might occur in the future. That is to avoid any disputes in the household or from things that are not desirable. Keywords: pregnancy test, islamic mariage, maslahah mursalah. Abstrak Salah satu tujuan dari pernikahan adalah untuk melanjutkan keturunan. Test deteksi kehamilan pranikah yang dipraktekkan KUA adalah terobosan baru yang mana dilatarbelakangi oleh keprihatinan masyarakat karena semakin maraknya pergaulan bebas yang berdampak kepada kehamilan di luar nikah. Maka dari itu, penulis memfokuskan 3 aspek pemasalahan dalam tesis ini, yakni: (1) Bagaimana pelaksanaan pernikahan di KUA Tembelang Jombang?, (2) Bagaimana urgensi test deteksi kehamilan pranikah di KUA Tembelang Jombang?, (3) Bagaimana pandangan maslahah mursalah terhadap praktek deteksi kehamilan pranikah?. Jenis penelitian dalam tesis ini merupakan penelitian lapangan. Sumber data dalam penelitian ini diperoleh langsung dari lapangan dengan pendekatan kualitatif yang mana data dikumpulkan lalu diolah dengan pendekatan deskriptif analitis. Apabila kebijakan ini dikaitkan dan dianalisis menggunakan teori maslahah mursalah, adanya kewajiban melakukan test deteksi kehamilan pranikah adalah memberi manfaat untuk banyak pihak yakni seluruh pihak akan dapat mengetahui secara detail hasil dari pemeriksaan tersebut. Selain memberikan kemanfaatan, kebijakan ini juga dapat menolak kemafsadatan yang mungkin saja terjadi di masa mendatang. Yakni menghindari adanya perselisihan dalam rumah tangga ataupun dari hal-hal yang tidak diinginkan. Kata kunci : Pemeriksaan kehamilan, pernikahan islam, maslahah mursalah